Manajemen Pengelolaan dan Pemilihan Alat Berat yang Tepat dalam Operasional Quarry Stone Cruser - Kerlima Hutagaol; Akhmad Faruq; Riza Fahlevi; Rachmaiyanti Rachmaiyanti; Budi Harta Winata (Lembaga Pengembangan Kinerja Dosen, 2025)
In the implementation of a toll road project, sufficient pavement material is needed, so based on the selection of the planned quarry location, one of the mountains or hills that can be taken stone material to support the project is chosen. In carrying out quarry crusher stone operations, it is necessary to provide several heavy equipment to support the work process. So in this journal discussion, the selection of the right tools in the operation of quarry crusher stone is emphasized.